Ultrafiltration in the management of refractory congestive heart failure. Issue 4 (April 1986) - Simpson, I A; Rae, A P; Simpson, K; Gribben, J; Boulton Jones, J M; Allison, M E; Hutton, I
Abstract : Ultrafiltration was performed in nine patients with congestive cardiac failure that was refractory to conventional medical treatment. A mean of 12 X 7 litres of fluid was removed, and there was a sustained symptomatic improvement in all patients. Weight loss continued after ultrafiltration and a sustained increase in serum sodium concentration was also noted. A transient fall in right atrial pressure was seen only at four hours after ultrafiltration. No adverse haemodynamic effects were seen four and eighteen hours after fluid removal. Intracardiac dimensions measured by echocardiography remained unchanged. Ultrafiltration can be used to relieve symptoms in patients with refractory congestive heart failure and gross oedema.